Women and Drugs : A Sociological study - Dr. Khalid Hantoosh Sachit (مجلة اداب ذي قار)
The current field study presented by the researcher includes many theoretical approaches to understand the drug problem among women, relying on the feminist theory that explains the problem of crime among women from a feminist point of view. The researcher has depended upon international and local reports, especially reports and statistics of the Iraqi Ministry of Interior. Then, he has conducted a field study on women convicted of drug cases in the women’s prison in Baghdad, where his sample comprises (78) convicted of drug cases, of whom (36) are convicted of addiction cases and (42) are convicted in the field of promoting and commercial activity in the world of drugs. For this purpose, two questionnaires are designed with common questions for both groups. The social survey method is adopted in a comprehensive census method for all convicts in this correctional institution during the field study period, which has been at the end of 2024, where the number of tables extracted from the data obtained by the researcher with his tools amounted to about (42) tables, and its findings can be summarized as follows: